2007
DOI: 10.1017/is007011015jkt013
|View full text |Cite
|
Sign up to set email alerts
|

The noncommutative geometry of k-graph C*-algebras

Abstract: This paper is comprised of two related parts. First we discuss which k-graph algebras have faithful traces. We characterise the existence of a faithful semifinite lowersemicontinuous gauge-invariant trace on C * (Λ) in terms of the existence of a faithful graph trace on Λ.Second, for k-graphs with faithful gauge invariant trace, we construct a smooth (k, ∞)summable semifinite spectral triple. We use the semifinite local index theorem to compute the pairing with K-theory. This numerical pairing can be obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
147
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(148 citation statements)
references
References 33 publications
1
147
0
Order By: Relevance
“…This fact was noticed by Tomforde in [16] and later also utilized in [10] and [14]. Tomforde considers maps δ on vertices with values in (0, ∞) which satisfy the following two conditions and calls them graph traces on E.…”
Section: Positive Faithful and Canonical Traces On Leavitt Path Algmentioning
confidence: 91%
See 4 more Smart Citations
“…This fact was noticed by Tomforde in [16] and later also utilized in [10] and [14]. Tomforde considers maps δ on vertices with values in (0, ∞) which satisfy the following two conditions and calls them graph traces on E.…”
Section: Positive Faithful and Canonical Traces On Leavitt Path Algmentioning
confidence: 91%
“…Namely, in [14, Proposition 3.9], it has been shown that there is a bijective correspondence between faithful, C-valued graph traces on a countable, row-finite graph E and faithful, semifinite, lower semicontinuous, gauge invariant, C-valued traces on C * (E). In [14], a trace t on a C * -algebra A is defined as an additive map on the positive cone A + of A taking values in [0, ∞] such that t(ax) = at(x) for a nonnegative real number a and x ∈ A + and t(xx * ) = t(x * x) for all x ∈ A.…”
Section: Characterizations Of Positive and Faithful Canonical Tracesmentioning
confidence: 99%
See 3 more Smart Citations